Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1093/anatox/35.5.264
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Glucuronide, Ethyl Sulfate, and Ethanol in Urine after Intensive Exposure to High Ethanol Content Mouthwash

Abstract: To determine the degree of ethanol absorption and the resultant formation and urinary excretion of its conjugated metabolites following intensive use of high ethanol content mouthwash, 10 subjects gargled with Listerine(®) antiseptic 4 times daily for 3¼ days. First morning void urine specimens were collected on each of the four study days and post-gargle specimens were collected at 2, 4, and 6 h after the final gargle of the study. Urine ethanol, ethyl glucuronide (EtG), ethyl sulfate (EtS), and creatinine we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 0 publications
1
20
1
Order By: Relevance
“…EtG/EtS testing is no exception. In our study, the concentrations of EtG and EtS observed at 12 hrs post consumption were, with the exception of some anecdotal reports much higher than those reported with even strong extraneous exposure (e.g., hand sanitizers), wherein concentrations rarely exceed usual cut-offs (Bertholf et al, 2011, Costantino et al, 2006, Hoiseth et al, 2010, Musshoff et al, 2010, Reisfield et al, 2011b, Reisfield et al, 2011a). Some healthcare workers, who are exposed to alcohol containing hand washes repeatedly throughout the day, might be positive if tested shortly thereafter, which could be addressed by allowing a 12 hr or greater interval before testing.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…EtG/EtS testing is no exception. In our study, the concentrations of EtG and EtS observed at 12 hrs post consumption were, with the exception of some anecdotal reports much higher than those reported with even strong extraneous exposure (e.g., hand sanitizers), wherein concentrations rarely exceed usual cut-offs (Bertholf et al, 2011, Costantino et al, 2006, Hoiseth et al, 2010, Musshoff et al, 2010, Reisfield et al, 2011b, Reisfield et al, 2011a). Some healthcare workers, who are exposed to alcohol containing hand washes repeatedly throughout the day, might be positive if tested shortly thereafter, which could be addressed by allowing a 12 hr or greater interval before testing.…”
Section: Discussioncontrasting
confidence: 77%
“…Concerns about false positives consequent to extraneous exposure to ethanol containing products may have impeded wider acceptance of this potentially valuable tool for clinical research and care (Bertholf et al, 2011, Costantino et al, 2006, Hoiseth et al, 2010, Musshoff et al, 2010, Reisfield et al, 2011b, Reisfield et al, 2011a, Rosano and Lin, 2008, SAMHSA, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Repeated exposure to alcohols could lead to passive alcoholization, possibly inducing adverse biochemical effects [3]. Despite the increasing use of ABHRs as part of hand hygiene programs, only a few studies have assessed the issue of alcohol absorption following hand disinfection [8,9,10,11,12]. The studies conducted on ethanol-based hand rubs reported that repeated hand rubbing led to blood ethanol concentrations below those known to be harmful in humans [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…As with ethanol-based hand rubs, the authors found that the amounts absorbed via inhalation and/or dermal contact were very low and probably unlikely to induce adverse health effects. Reisfield et al [11,12] found that intensive use of ethanol-based sanitizer and mouthwash induces an increase in concentrations of urinary ethanol biomarkers (ethyl glucuronide and ethyl sulfate), leading to false-positive results related to ethanol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Further, they are reported to remain detectable in urine for 1 – 2 days or longer (Palmer, 2009). However, reports of over-sensitivity to incidental alcohol exposure through hand sanitizer (Reisfield, Goldberger, Crews, et al, 2011), trace amounts of alcohol in some foods (Musshoff, Albermann, & Madea, 2010), and mouthwash (Costantino, Digregorio, Korn, Spayd, & Rieders, 2006; Reisfield, Goldberger, Pesce, et al, 2011) have led to suggestions in a recent SAMHSA review for more research regarding cutoff values that balance sensitivity and specificity in research contexts (Substance Abuse and Mental Health Services Administration, 2012). This 2012 SAMHSA review also noted substantial need for research regarding the role of individual factors such as gender, age, or medical condition to aid in interpretation of these biomarkers.…”
Section: Introductionmentioning
confidence: 99%